Peningkatan Prestasi Belajar Aplikasi Pengolah Angka Dengan Menggunakan Model Pembelajaran Berbasis Masalah (Problem Based Learning ) Pada Siswa Kelas X TKJ SMK Negeri Kalitengah Tahun Pelajaran 2021/ 2022 - Huda, Khoirul (MADINAH, 2022)
To be able to learn something well, we need to hear, see, ask questions about it, and discuss it with others. Not only that, students need to "do it", ie describe something in their own way, show examples, try to practice skills and do assignments that demand the knowledge they have acquired. The problems to be studied in this study are: (1) Can the application of problem-based learning models increase student achievement? (2) How does the problem-based learning model influence students' learning motivation? The objectives of this classroom action research are: (1) Want to know the increase in student achievement after the implementation of problem-based learning models (2) to find out how the impact of problem-based learning models on increasing student motivation. This study used three rounds of action research. Each round consists of four stages: design, activity and observation, reflection, and revision. The target of this research is class X TKJ students of Kalitengah State Vocational School. The data obtained is in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis, it was found that student achievement increased from cycle I to cycle III, namely cycle I (64.00%), cycle II (76.00%), cycle III (88.00%) and also had a positive impact on motivation. student learning from cycle I to cycle III namely, cycle 1 interest (14.7%) attention (37.5%) participation (33.30%), cycle II interest (62.50%) attention (58.30%) ) participation (58.30%), cycle III, interest (83.30%) concern (79.20%) participation (79.20%) The conclusions from this study are that the problem-based learning model can improve student learning achievement and have a positive impact on the learning motivation of Class X TKJ students at Kalitengah State Vocational School and this learning model can be used as an alternative learning number processing application.